Cellulose‐Nanofiber‐Reinforced Rubber Composites with Resorcinol Resin Prepared by Elastic Kneading. Issue 12 (16th December 2021) - Noguchi, Toru; Bamba, Yasuo; Miura, Takashi; Iwamoto, Rie; Endo, Morinobu; Isogai, Akira
Abstract : Inside Cover : In article number 2100483 by Toru Noguchi, Akira Isogai, and co‐workers, a dried cellulose nanofiber/resorcinol resin (CNF/resorcinol) is prepared by oven drying of the aqueous mixtures. The dried CNF/resorcinol is added to rubber sheets, and the mixtures are kneaded with high shear forces to prepare composites. The tensile strength and Young's modulus remarkably increases to 24 and 82 MPa, respectively, for the composites containing ≈10 vol% TEMPO‐CNFs.